Synthesis and fluorescence properties of a full set of extended RNA base analogues - Sabale, Pramod M.; Nuthanakanti, Ashok; Srivatsan, Seergazhi G. (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2013)
The synthesis and photophysical characterization of a complete set of fluorescent RNA base analogues derived by conjugating benzofuran moiety at the 5- and 8-positions of pyrimidine and purine bases, respectively, are described. Benzofuran-modified pyrimidine and purine ribonucleoside analogues exhibit Contrasting fluorescence properties. Pyrimidine analogues are moderately emissive with emission maximum in the visible region, and importantly, are highly sensitive to solvent polarity and Viscosity changes. On the other hand, purine analogues are highly emissive and are minimally affected by solvation. and viscosity effects. Thorough photophysical analysis reveals that the pyrimidine and purine ribonucleosides displaying distinct and-probe-like fluorescence properties could be useful in designing nucleic acid based biophysical tools to study nucleic acid structure and function.
Keywords: Environment sensitive probes; Fluorescence probes; Fluorescence spectroscopy; Nucleic acids; Ribonucleoside analogues